Timing selection for loosened tooth fixation based on degree of alveolar bone resorption: a finite element analysis - Zhang-yan Ye; Hao Ye; Xi-xi Yu; Yong Wang; Li-jun Wu; Xi Ding (BMC Oral Health, 2022)
Abstract Objective This study aimed to evaluate timing of fixation to retard bone absorption using finite element analysis(FEA). Methods Volunteer CT images were used to construct four models of mandibles with varying degrees of alveolar bone resorption. By simulating occlusal force loading, biomechanical analysis was made on the periodontal membrane, tooth root and surrounding bone (both cancellous and cortical) of mandibular dentition. Results The von Mises stress value of the periodontal structures was positively related with the degree of alveolar bone resorption, and the von Mises stress at the interface between the periodontal membrane and tooth root was increased significantly in moderate to severe periodontitis models. The von Mises stress at the interface between the periodontal cortical bone and cancellous bone was increased significantly in the severe periodontitis model. And the von Mises stress value with oblique loading showed significantly higher than vertical loading. Conclusion Teeth with moderate to severe periodontitis, loosened tooth fixation can be used to retard bone absorption.